Alternative Assessment Approaches in Primary English Language Classrooms (Journal of NELTA, 2014)
In recent years, the philosophy and implementation of alternative assessment in primary classrooms have become the center of discussion and debate in the educational sector among scholars, educators, and stakeholders in many countries including Nepal. This paper presents a study on the alternative assessment practices in primary English language classrooms based on a qualitative approach. The aim of this paper is to provide an overview of alternative assessment, the paradigm shift from traditional assessment to alternative assessment, and some insights on the practices of alternative assessment prevalent in the selected private schools in Kathmandu valley along with teachers’ perceptions and challenges. DOI: http://dx.doi.org/10.3126/nelta.v18i1-2.10337 Journal of NELTA, Vol 18 No. 1-2, December 2013; 148-163